ANALISIS POTENSI KOMERSIALISASI SUMBER MATA AIR JOLOTUNDOOLEH MASYARAKAT JOLOTUNDO - Deddy Ahmad Fajar; Farah Nur Fauziah (El-Idaarah, 2023)
Petirtaan Jolotundo is a spring that was built into a lakeattack by the Ancient Medang kingdom. The benefits of Jolotundo springs arrivecurrently felt by society. The Village Government established HIPAMas an organization that regulates water distribution to the community. There ispotential for commercialization of springs for community welfare. HIPAMhas a turnover of IDR 5,930,000 per month which is used asspring water distribution operations and community welfare. ConclusionIn this research, commercialization of Jolotundo springs can be achievedprovide welfare to the community and provide servicesbetter.